Uso de índices quantitativo e qualitativo como métodos de avaliação da qualidade do solo cultivado com cana-de-açúcar - Cardoso, Denise Campos (Universidade Federal de São Carlos, 2022)
The transformation of natural systems into agricultural systems tends to cause damage to soil quality due to the forms of management used for cultivation, thus causing soil degradation and productive potential loss provided by it, which leads to crop productivity losses. Strategies to monitor soil quality and mitigate degradation caused by management systems are important. Therefore, soil quality indices are tools that help in decision making. With this in mind, the present work aims to evaluate the quality of the soil cultivated with sugarcane at the Center for Agricultural Sciences of the Federal University of São Carlos (CCA - UFSCar) through two quantitative and visual soil quality indices (IQS), which were based on physical, chemical and morphological data obtained for each block of the campus. For the evaluation, different land uses (forest, Environmental Protection Area (APA) and sugarcane (CA)) and soil classes (Latossolo Vermelho, Nitossolo Vermelho and Argissolo Vermelho) were considered. The IQS Quantitative was obtained based on the following indicators: organic matter, texture, CTC, hydraulic conductivity, phosphorus, potassium, aluminum saturation and pH, while for the IQS Visual the following indicators were considered: color, structure, consistency, presence of root and biological channels. Both indices sought to reflect the soil's ability to provide better conditions for plant growth. Weights and scores were then assigned to each indicator according to plant growth potential. Finally, the scores of the indicators were applied to an equation that provides the final index. From the classification obtained in each index, it was possible to verify that the forest land use obtained the best score for the two evaluated indices, which is the only point of correlation between them, since each index had a different ranking of the land uses. Soil class was also not a determining factor for soil performance, as soils of the same class did not have indices with approximate values. For IQS areas that have limitations, conservation practices such as level planting, green manuring and no-till are recommended in order to ensure greater soil and water conservation.
Quantitative and qualitative indices use as soil quality assessment methods cultivated with sugarcane
Keywords: Índice de qualidade do solo; Avaliação visual do solo; Avaliação quantitativa do solo; Indicadores; Soil quality index; Soil visual assessment; Soil quantitave assessment; Indicators; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO